Epigenetic regulation of intracellular branched-chain amino acid homeostasis maintains a normal lifespan - Sejung Park; Yan Liu; Suji Lim; Hong-Yeoul Ryu; Seong Hoon Ahn (iScience)
Summary: Cells experience a progressive decline in function and lifespan, accompanied by epigenetic changes. Here, we show that intracellular BCAA (icBCAA) homeostasis is regulated by histone H3K4 and H3K121 in budding yeast. Using a comprehensive H3/H4 mutant library, we identified residues essential for lifespan maintenance linked to BCAA metabolism. Among these, H3K4A/R and H3K121A mutations led to significant transcriptional changes in genes involved in BCAA biosynthesis and catabolism, accompanied by abnormally elevated icBCAA levels. Consistent with the upregulation of BAT1, ILV6, and ADH1 genes in the H3K121A mutant, chromatin immunoprecipitation revealed increased H3K4me3 at their promoters. The genetic perturbation of BAT1 and BAT2 restored icBCAA balance and partially rescued lifespan defects in H3K4 or H3K121 mutants. Additionally, H3K4 and H3K121 mutations affected lifespan regulation through TORC1 signaling. Our findings suggest that the epigenetic control of BCAA metabolism, specifically through the modification of histone residues, contributes to maintaining metabolic homeostasis and replicative lifespan.